2019
DOI: 10.3390/su11226214
|View full text |Cite
|
Sign up to set email alerts
|

The Corporate Sustainability Strategy in Organisations: A Systematic Review and Future Directions

Abstract: The corporate sustainability strategy in organisations is a current topic and set in Agenda 2030 for sustainability, and so this study aims to map the literature on the subject through a bibliometric analysis. From 97 documents identified and analyzed, the results obtained show the fragmentation and hiatus between the planning of a global strategy and inclusion therein of a sustainable strategy. Furthermore, these results provide the construction of a framework as an auxiliary tool for managers of different or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 110 publications
(128 reference statements)
2
48
0
1
Order By: Relevance
“…To understand the capillarity of the research on the 2030 Agenda, a first step is to take a look to systematic reviews and bibliometric analyses in the topic. In our research, we have identified 27 reviews so far, where the authors focus on studies of the implementation and the achievement of the SDGs (Barrantes Briceño and Almada Santos, 2019; Guha and Chakrabarti, 2019; Gusmão Caiado et al, 2018; Hristov and Chirico, 2019; Khan et al, 2019; Maroyi, 2018; Merino‐Saum et al, 2018; Omer and Noguchi, 2020; Schiappacasse and Müller, 2018; Zhang et al, 2019), on specific topics and collectives within the Agenda (Baum et al, 2016; Del Pino et al, 2019; Giné‐Garriga et al, 2017; Hartmann et al, 2016; Majinge and Mutula, 2018; Mathez‐Stiefel et al, 2017; Matilla et al, 2018; Simcock and Wittich, 2019; Swamy et al, 2018), on traditional fields of knowledge, now reconsidered in the light of the 2030 Agenda (Elfert, 2019; Rodrigues and Franco, 2019; Storey et al, 2017), and even on contributions to the field of knowledge from researchers in specific regions or countries (Körfgen et al, 2018; Staszkiewicz, 2019).…”
Section: The 2030 Agenda For Sustainable Developmentmentioning
confidence: 99%
“…To understand the capillarity of the research on the 2030 Agenda, a first step is to take a look to systematic reviews and bibliometric analyses in the topic. In our research, we have identified 27 reviews so far, where the authors focus on studies of the implementation and the achievement of the SDGs (Barrantes Briceño and Almada Santos, 2019; Guha and Chakrabarti, 2019; Gusmão Caiado et al, 2018; Hristov and Chirico, 2019; Khan et al, 2019; Maroyi, 2018; Merino‐Saum et al, 2018; Omer and Noguchi, 2020; Schiappacasse and Müller, 2018; Zhang et al, 2019), on specific topics and collectives within the Agenda (Baum et al, 2016; Del Pino et al, 2019; Giné‐Garriga et al, 2017; Hartmann et al, 2016; Majinge and Mutula, 2018; Mathez‐Stiefel et al, 2017; Matilla et al, 2018; Simcock and Wittich, 2019; Swamy et al, 2018), on traditional fields of knowledge, now reconsidered in the light of the 2030 Agenda (Elfert, 2019; Rodrigues and Franco, 2019; Storey et al, 2017), and even on contributions to the field of knowledge from researchers in specific regions or countries (Körfgen et al, 2018; Staszkiewicz, 2019).…”
Section: The 2030 Agenda For Sustainable Developmentmentioning
confidence: 99%
“…Thematic incubators have huge potential to act as the platform which connects these different approaches to corporate sustainability. The term incubator is derived from the basic meaning of the term nurturing, which is to develop small companies in a protected environment [16]. Incubators are a perfect way to enhance partnership and co-design innovation and knowledge products to enhance inclusion of sustainability factors by a corporate.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The concept of the incubator originated in the early 1950s in the United States. The term incubator is derived from the root term, which means nurturing; incubators develop small companies in a protected environment (Rodrigues and Franco, 2019). Incubators provide support to budding entrepreneurs in the early start and development of their ideas.…”
Section: Innovation and Incubationmentioning
confidence: 99%